Management of root-rot of mungbean caused by Macrophomina phaseolina through seed treatment with fungicides - MUJEEBUR RAHMAN KHAN*, SHUMAILA SHAHID and (Indian Phytopathology, 2016)
An experiment was conducted to determine the effect of seed treatment with five fungicides viz., carbendazim, captan, thiram, mancozeb and vitavax against root-rot of mungbean caused by Macrophomina phaseolina under pot condition. The results of the present study proved that all the fungicides reduced the root-rot severity and subsequently improved the growth and yield of infected mungbean plants to a greater or lesser extent. Plants grown in inoculated pots without fungicides treatment exhibited significant (Pâ‰¤0.05) decline in the plant growth (32-45%) and yield (36%) due to greater root-rot severity. The relative efficacy of fungicides proved carbendazim to be the most effective fungicide in reducing root-rot severity (44%) and increasing plant growth (25-33%) and yield (27%). Captan was next in effectiveness and caused 38% reduction in rootrot severity with 24% increase in yield (Pâ‰¤0.05). Mancozeb was least effective which caused lowest decrease in disease severity (27%) and minimum increase in plant growth (11-13%) and yield (11%). Total chlorophyll, total carotenoid and leghaemoglobin content as well as nodulation in roots was also significantly improved due to fungicide treatments (P0.05). Similarly, pathogen population in soil was 45-60% lower in the pots treated with the fungicides than untreated pots, of which, lowest was recorded with carbendazim.